El silencio en la vida de las mujeres: entre la opresión y la resistencia - Chávez Trejo, Edith Guadalupe (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
In this research, I investigate and analyze the conditions in which silence, in women's lives, can be a means of resistance to patriarchal rationality. It is structured in three chapters. The first is entitled “The historical silencing of women”, in which I set the scene for the research by reviewing some arguments about the historical silencing of women as a means of patriarchal control and domination, in the face of which the feminist call to break the silence is essential. I also establish the conceptual difference between silence and silencing; I maintain that silence in itself is not oppressive. In the second section, entitled “Silence as a means of resistance”, I explore the relationship between resistance, power, and silence. Given that these terms have different meanings, it is important to note that I draw on the theoretical foundations for the conceptual approach from Brown (1996), Butler (2017), and Foucault (1970/1992, 1977/2011). In chapter 3, entitled “Silence and Listening to Oneself for Subjective Transformation in the Face of Patriarchal Rationality. A view from philosophy and psychoanalytic and feminist clinical practice”, I establish a dialogue between philosophy, silence in the psychoanalytic method, and feminist theory. This is a theoretical thesis and takes into account the postulates of feminist epistemology (Blázquez, 2010) at all times. In addition, each chapter weaves together theory and everyday examples that are analyzed using the methodological tool of critical discourse analysis from a feminist point of view (Blázquez, 2010). As part of my findings, I argue that silence can be a means of resistance to patriarchal rationality when it relates to choice and will and allows one to listen to oneself; when it serves as a refuge from power; and when the silence of the spoken word does not translate into an absence of thought and, in that sense, does not stem from prior oppressive silencing.

En esta investigación indago y analizo las condiciones en las que el silencio, en la vida de las mujeres, puede ser un medio de resistencia ante la racionalidad patriarcal. El trabajo consta de tres capítulos. El primero tiene por título “El silenciamiento histórico de las mujeres”, en él pongo en situación la investigación al recuperar algunos argumentos acerca del silenciamiento histórico de las mujeres como medio de control y dominación patriarcal ante el cual el llamado feminista a la ruptura del silencio es imprescindible. Además, establezco la diferencia conceptual entre silencio y silenciamiento y, sostengo, el silencio en sí mismo no es opresivo. En el segundo apartado, titulado “El silencio como medio de resistencia”, indago la relación entre resistencia, poder y silencio. Dado que estos términos tienen diferentes concepciones, es importante señalar que las bases teóricas para el abordaje conceptual las recupero desde Brown (1996), Butler (2017) y Foucault (1970/1992, 1977/2011). En el capítulo 3, titulado “El silencio y la escucha de sí para la transformación subjetiva ante la racionalidad patriarcal. Una mirada desde la filosofía y la clínica psicoanalítica y feminista”, establezco un diálogo entre la filosofía, el silencio en el método psicoanalítico y la teoría feminista. Esta es una tesis teórica y contempla en todo momento los postulados de la epistemología feminista (Blázquez, 2010). Además, en cada capítulo se tejen teoría y ejemplos cotidianos que son analizados con la herramienta metodológica del análisis crítico del discurso desde el punto de vista feminista (Blázquez, 2010). Como parte de los hallazgos sostengo que el silencio puede ser un medio de resistencia ante la racionalidad patriarcal cuando se relaciona con la elección, la voluntad y permite la escucha de sí; cuando sirve como refugio ante el poder y cuando el silencio de la palabra oral no se traduce en ausencia de palabra pensada y en ese sentido, no proviene de un silenciamiento opresivo previo.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2025-1739; Silenciamiento de las mujeres; Racionalidad patriarcal; Resistencia; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19514